Pengaruh perubahan sudut camshaft terhadap performa mesin sepeda motor sebagai upaya efisiensi energi - Lukito Dwi Yuono; Eko Budiyanto (TURBO [Tulisan Riset Berbasis Online], 2020)
The role of the camshaft (noken as) is very important, including determining the time to open the valve, regulating the length of the valve opening duration, determining the overlap inlet and exhaust valve duration, as well as being a major component of the engine's working system. Modification of the camshaft angle is expected to be able to increase the efficiency of the combustion of fuel entering the combustion chamber and increase compression pressure in the combustion chamber so that it can improve volume quality of fuel entering the combustion chamber and can provide greater power to the engine rotation when in use. The purpose of this study was to determine the effect of camshaft angle changes on motorcycle engine performance and determine the effect of the camshaft duration on fuel consumption. The method that will be used in this research is to provide variations in angular changes on the camshaft of 20, 40, 60.Then test the dyno test on each variable. The result, the highest torque is the camshaft 40 variation with a value of 8.25 Nm. The highest power is in variation 40 with the highest number of 8.76 PS. Acceleration with the fastest time is obtained in camshaft 40 variations with a time of 14.2 seconds at a speed of 100 km/h. As well as the most efficient fuel consumption is at variation 20 with 150 ml fuel consumption.Keywords: Angle, camshaft, and engine performance.